Eksegese is 'n spel - JH le Roux (Acta Theologica)
This article is devoted to a different understanding of exegesis. It is intended as a contribution to the ongoing South African debate. First of all the South African way of exegesis is discussed. It is interpreted and described as a typical Cartesian search for fixed foundations. Then Hans-Georg Gadamer's view of play is employed to depict a different kind of approach. It is argued that an understanding of exegesis as a way of playing with the text can be of great value.